Development of autonomous miniature mobile robot for swarm applications - Arvin, Farshad (2010)
Biological swarm is a fascinating behavior of nature that has been successfully applied to solve human problems especially for robotics application. The high economical cost and large area required to execute swarm robotics scenarios does not permit experimentation with real robots. Modeling and simulation of mass numbers of these robots are extremely complex and often inaccurate. This research describes the design decision and presents the development of an autonomous miniature mobile robot called AMiR, for swarm robotics research and education. Two criteria for designing a swarm platform are the feasibility of mobile robot as an autonomous system and the amenability of inter-robots behavior in swarm applications. In the design phase, suitable components based on three main principles which are functional ability, low-cost, and local modules were selected. Several common platforms were studied and AMiR prototype was designed. The large number of robots in these systems allows designing of an individual AMiR unit with simple perception and mobile abilities. Hence a large number of robots can be easily and economically feasible to be replicated (around 310 MYR per unit). AMiR has been designed as a complete platform with supporting software development tools for robotics education and researches. Inter-robot communication is a significant issue in swarm applications. Short range infrared communication was selected to transmit robot’s messages. Two different modulation which are amplitude and frequency shift keying techniques were implemented on AMiR and features of each technique were discussed. Additional modules are mounted on top of main board to implement several behaviors inspired from nature. Three different swarm scenarios based on collective behaviors were performed and effective parameters in each behavior were discussed. The experimental results demonstrate the feasibility of using this robot to implement swarm robotic applications.